Pengaruh Harga, Kualitas Produk dan Word of Mouth Terhadap Keputusan Pembelian Pada E-Commerce Shopee (Pada Mahasiswa Manajemen Universitas Islam Malang 2019) - Mohamad Ramadhany Idris; Agus Widarko; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine the effect of price, product quality and word of mouth on purchasing decisions through e-commerce Shopee. Quantitative methods are used in this type of research. This research was conducted on Shopee customers where the sample determined was students of the Islamic University of Malang class of 2019. The sampling method used in this study was a non-probability sampling method, especially the British sampling method, where the sample obtained must meet certain withdrawals. depending on the research objectives. . Questionnaires are used as a method or collection tool in this quantitative research. Based on the results of this study, (1) price has a strong influence on purchasing decisions, (2) product quality has a strong influence on purchasing decisions, and (3) word of mouth has a strong influence on purchasing decisions. Keywords: Price, Product Quality, Word Of Mouth